Functio Laesa: Cancer Inflammation and Therapeutic Resistance - Liu, Mingen (J Oncol Pract, 2017)
Tumor, calor, rubor, and dolor describe four cardinal signs of inflammation. The fifth—functio laesa, or loss of function—was promulgated by Rudolf Virchow, who, in the 19th century, also noted an intricate link between inflammation and cancer. However, the role of cancer inflammation in driving loss of therapeutic efficacy has only recently been fully appreciated, as a result of molecular and immunohistochemical approaches applied in clinical medicine and the availability of novel agents for modulating inflammation. This review focuses on clinical evidence from solid malignancies that have shaped our view of how the immune system regulates cancer development, progression, and response to treatment. Understanding the multifaceted relationship between inflammation and patient outcomes has the potential to advance prognostic tools and uncover therapeutic opportunities for improving clinical outcomes.